Numerical Analysis of the Wake Interactions Between Two Tandem Cylinders at a Reynolds Number of 1×10^5 - Tambunan, Muhammad Fadli; Cut, Banta; A.Abdullah, Nasruddin (Fakultas Teknik Universitas Samudra, 2025)
Circular cylinders are a geometric shape widely utilized in engineering applications such as electricity poles, offshore piles, subsea pipelines, and heat exchangers, where the drag force fluctuations experienced by two tandem-arranged cylinders are known to be determined by the longitudinal spacing ratio (L/D); previous studies were conducted at a Reynolds number of 6.5 x 104. This foundation led to the initiative for further numerical simulation research aimed at analyzing the effect of L/D variations (1.5, 2.0, 3.0, and 4.0) on the flow characteristics around two such cylinders at a higher Reynolds number (1X10), utilizing a cylinder diameter (d) of 25 mm within a narrow square channel (H = 300 mm and L = 1500 mm). This study was performed using 2D unsteady RANS via Ansys Fluent Student R2 2021, employing a structured mesh and the k-ω SST turbulence model. The results revealed that the L/D = 1.5 variation shows a significantly lower rear pressure compared to L/D = 2.0, 3.0, and 4.0, where the largest pressure difference between the front (high) and the rear (very low and negative) indicates the highest pressure drag, a characteristic dominated by earlier flow separation and a large wake. Conversely, the L/D = 3.0 variation demonstrated the lowest upstream cylinder CD value (0.734) among all variations, suggesting optimal reduction, while the lowest downstream cylinder CD value (0.209) was recorded at the L/D = 1.5 spacing.